MODELLING & OPTIMIZATION OF CO2 EMISSION IN PEFB DERIVED BIO-SYNTHETIC NATURAL GAS PRODUCTION VIA PHYSICAL ABSORPTION - MOHAMAD AFIQ, MOHD ASRUL (Universiti Malaysia Sarawak (UNIMAS), 2020)
The final year project titled modelling and optimisation of carbon dioxide (CO2) emission in palm empty fruit bunch (PEFB) derived bio-synthetic natural gas production via physical absorption has been reported. The anthropogenic CO2 emission has responsibility for global warming and climate changes which contributed significantly by the heavy utilisation of conventional fossil fuel power to meet the need of humankind. Biomass is a potential alternative source of energy to replace the dependency of fossil fuel reserves that expected to undergo long term depletion and considering the environmental conservation through CO2 natural emission life cycle. Biomass conversion to energy even has no exception in releasing CO2 which could be mitigated by the introduction of biogas purification unit to be incorporated with waste to energy (WtE) technology. The massive increase of agriculture waste accumulation in Malaysia like PEFB can be inverted into a potential feedstock of thermal WtE plant to generate valuable and clean bio-synthetic natural gas for electricity and heat utility. Considering the sluggish development of WtE in Malaysia, the mathematical model on the physical absorption of CO2 from dried PEFB derived bio synthetic gas production is established and optimised to achieve a green manufacturing tariff including the model capability to serve 95 – 98 % CO2 removal efficiency and finalised operating design of modelled CO2 absorber is optimal for the dried PEFB derived bio-synthetic natural gas with CO2 concentration at 40.051 mole % and below. The performance of the validated model for CO2 absorption by physical solvent dimethyl ether polyethylene glycol (DEPG) could be optimised by carrying out sensitivity analysis based on the variation of temperature, operating pressure and liquid to gas (L/G) stream flowrate ratio. The modelling finding has shown that the satisfactory CO2 reduction efficiency of CO2 physical absorption in the PEFB derived bio synthetic gas production could be met optimally at T = 31.0 oC, P = 1.6 kPa and L/G = 1:1.